Awareness of cybersecurity: a case study in UiTM Negeri Sembilan branch, Seremban Campus / Adlina Kamalulail ... [et al.] - Kamalulail, Adlina; Abdul Razak, Nur Ezzatul Nadia; Omar, Siti Aisyhah; Mohamed Yusof, Noreha (2022)
Cybersecurity is a problem that is rarely discussed by the public, especially among university students in Malaysia. This study aims to determine the significant differences of cybersecurity awareness between genders and to investigate the significant predictors of the cybersecurity awareness. This study adopts a cross-sectional methodology among UiTM Negeri Sembilan, Seremban Campus students (n=201, 19 to 25 years old) using a questionnaire. The results show that male and female students have the same level of cybersecurity awareness. Meanwhile, gender, age, marital status, faculty, type of social media used, hours spent on social media, attitude and environmental factors do not in any way affect the awareness of cybersecurity among students. The results further show that it is only the knowledge factors that differentiate cybersecurity awareness among them.